3PL, 4PL and insourcing logistics - Mauro Vivaldini (GEPROS: Gestão da Produção, Operações e Sistemas, 2015)
Logistics services have evolved and changed over time, especially in the hiring of them according to the concepts of 3PL (third party logistics), 4PL (fourth party logistics) or insourcing logistics. 3PL service is a consolidated business, 4PL is an option for outsourcing logistics and has already been adopted by some organizations, and insourcing logistics suggests the return of these activities being internalized by companies, which is still a relatively unexplored subject in logistics literature. Analyzing these themes in the literature, this study updates the view on them and proposes a conceptual framework that classifies the different models of logistics services, showing the different options that can be adopted to help the company decide how to run their logistics services.